Katie and Peter : Moving On - Herbert, Emily (London John Blake Publishing Ltd., 2010)
The saga continues. Following their rather public separation and messy divorce the tabloids simply cannot leave the feuding pair alone. With accusations and underhand comments trading camps on a daily basis Katie and Peter are never far from the front pages. Seeking "closure" on her relationship with Peter, Katie returned to I'm a Celebrity Get Me Out of Here where she battled her way through countless disgusting bush tucker trials before walking out on the show. With a rumored proposal and an on-air announcement that their relationship was over, Katie's on/off relationship with cage fighter Alex Reid has added another dimension to the Peter and Katie picture. Offering an olive branch to Alex, Peter has turned his attentions to his music career and his Revelation Tour is a complete sell out with extra dates added. With both Katie and Peter continuing on their separate paths could they really, finally be moving on, or is this saga set for another chapter?
Include Color Illustrations.
Keywords: Models (Persons) -- Singers -- Australia